EMPOWERING INVESTMENT DECISIONS THROUGH FINANCIAL LITERACY AND GOVERNMENT REGULATIONS ON MSMES - Ariwangsa, IGN Oka; Putra, Komang Widhya Sedana; Laksmi , Kadek Wulandari (ANALISIS, 2025)
The two major factors that influence investment decisions are an individual's financial literacy and the regulatory framework in existence. In the wake of fast-growing investments, especially among MSMEs in Denpasar, it is important to understand how financial literacy and government regulations influence investment decisions. The aim of the paper is to analyze the influence of financial literacy on investment decisions, and the contribution of government policies to this influence. The design used in this study is a quantitative approach with questionnaires given out to 200 respondents that perform investment activities within Denpasar. In analyzing data, PLS-SEM is used to test the hypotheses stated in this research paper. The result from the study revealed that financial literacy has a significantly positive influence on the investment decision. Furthermore, government regulations have a moderating role but with a relatively smaller effect, which means that effective regulation can strengthen the positive influence of financial literacy on investment decisions.